Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Guharajan, Roshan; Abrams, Jesse F.; Abram, Nicola K.; Lim, Hong Ye; Clements, Gopalasamy Reuben *; Deere, Nicolas J.; Struebig, Matthew J.; Goossens, Benoit; Gardner, Penny C.; Brodie, Jedediah F.; Granados, Alys; Teoh, Shu Woan; et al. (Springer, 2023)
Habitat loss, habitat degradation and poaching threaten the survival of large mammals in Southeast Asia. Studies on these threats tend to focus on small spatial scales (i.e. a protected area), precluding region-wide species assessments that can inform conservation management. Using existing camera trap data, we constructed occupancy models to understand patterns of habitat use as well as predict the distribution of sun bears Helarctos malayanus across Sabah, Malaysian Borneo. We found that bear distribution was related to above-ground carbon density and human settlement density, characteristics that describe the quality of bear habitat and a potential threat of poaching, respectively. Only half of sun bear distribution in Sabah falls within protected areas. Outside of protected areas, we predicted the reduction of sun bear distribution under simulated future conventional selective logging (forest degradation) and industrial tree plantation expansion (forest loss) scenarios. In the scenario involving forest degradation, sun bear distribution across Sabah only decreased by ~ 4%, supporting existing evidence that sun bears are resilient to selective logging impacts. Forest loss, however, had a larger impact, reducing sun bear distribution by ~ 11% in the scenario involving high forest loss. We recommend a focus on long term monitoring of sun bear habitat suitability trends, especially outside protected areas, along with strong anti-poaching efforts. Our study demonstrates the utility of pooling existing camera trap data to understand region-wide species distributions that could assist in setting conservation priorities.